2021
DOI: 10.1038/s41386-021-01244-7
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and glucose metabolism with olanzapine and a combination of olanzapine and samidorphan: exploratory phase 1 results in healthy volunteers

Abstract: A combination of olanzapine and samidorphan (OLZ/SAM) received US Food and Drug Administration approval in May 2021 for the treatment of adults with schizophrenia or bipolar I disorder. OLZ/SAM provides the efficacy of olanzapine, while mitigating olanzapine-associated weight gain. This exploratory study characterized the metabolic profile of OLZ/SAM in healthy volunteers to gain mechanistic insights. Volunteers received once-daily oral 10 mg/10 mg OLZ/SAM, 10 mg olanzapine, or placebo for 21 days. Assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…The trials have documented the good tolerability of OLZSAM and indicated that the incidence of adverse events with either OLZSAM or OLZ is comparable. 26-28,30,31 Haddad et al also had documented that OLZSAM exhibited fewer adverse effects than OLZ, and the same has been substantiated by Jawad et al, as they observed that in short-term studies, the addition of the µ-opioid receptor antagonist did not alter the safety profile of the OLZ. 15,20 Interestingly, we observed that the incidences of various adverse events were either high in the OLZ group or the OLZSAM group.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…The trials have documented the good tolerability of OLZSAM and indicated that the incidence of adverse events with either OLZSAM or OLZ is comparable. 26-28,30,31 Haddad et al also had documented that OLZSAM exhibited fewer adverse effects than OLZ, and the same has been substantiated by Jawad et al, as they observed that in short-term studies, the addition of the µ-opioid receptor antagonist did not alter the safety profile of the OLZ. 15,20 Interestingly, we observed that the incidences of various adverse events were either high in the OLZ group or the OLZSAM group.…”
Section: Discussionmentioning
confidence: 74%
“…36 Even though we wished to include trials of high quality, two of them (Toledo et al and Silverman et al) had a high risk of bias, thus affecting the results. 28,31 On the whole, the certainty of evidence generated in this meta-analysis for the selected endpoints was of moderate to high quality, except for the incidence of weight gain, headache, dry mouth, and any adverse event, wherein the certainty ranged from low to very low (Tables 2 and 3), which again can be attributed to these two trials having a high risk of bias. Furthermore, the overall certainty was reduced as the sample size required to achieve optimal information was inadequate in these trials.…”
Section: Events (Especially Weight Gain) the Outcomes Are Based On We...mentioning
confidence: 85%
See 3 more Smart Citations